Systematic review and economic evaluation of Helicobacter pylori eradication treatment for non-ulcer dyspepsia. Issue 7262 (16th September 2000) - Moayyedi, Paul; Soo, Shelly; Deeks, Jonathan; Forman, David; Mason, James; Innes, Michael; Delaney, Brendan
Abstract: Objectives: To evaluate efficacy and cost effectiveness of Helicobacter pylori eradication treatment in patients with non-ulcer dyspepsia infected with H pylori . Design: Systematic review of randomised controlled trials comparing H pylori eradication with placebo or another drug treatment. Results were incorporated into a Markov model comparing health service costs and benefits of H pylori eradication with antacid treatment over one year. Data sources: Six electronic databases were searched for randomised controlled trials from January 1966 to May 2000. Experts in the field, pharmaceutical companies, and journals were contacted for information on any unpublished trials. Trial reports were reviewed according to predefined eligibility and quality criteria. Main outcome measures: Relative risk reduction for remaining dyspeptic symptoms (the same or worse) at 3-12 months. Cost per dyspepsia-free month estimated from Markov model based on estimated relative risk reduction. Results: Twelve trials were included in the systematic review, nine of which evaluated dyspepsia at 3-12 months in 2541 patients. H pylori eradication treatment was significantly superior to placebo in treating non-ulcer dyspepsia (relative risk reduction 9% (95% confidence interval 4% to 14%)), one case of dyspepsia being cured for every 15 people treated. H pylori eradication cost £56 per dyspepsia-free month during first year after treatment. Conclusion: H pylori eradication may be cost effective treatment for non-ulcer dyspepsia in infected patients but further evidence is needed on decision makers' willingness to pay for relief of dyspepsia.